2019
DOI: 10.1002/adma.201900321
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared‐II Molecular Dyes for Cancer Imaging and Surgery

Abstract: Fluorescence bioimaging affords a vital tool for both researchers and surgeons to molecularly target a variety of biological tissues and processes. This review focuses on summarizing organic dyes emitting at a biological transparency window termed the near‐infrared‐II (NIR‐II) window, where minimal light interaction with the surrounding tissues allows photons to travel nearly unperturbed throughout the body. NIR‐II fluorescence imaging overcomes the penetration/contrast bottleneck of imaging in the visible reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
507
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 737 publications
(558 citation statements)
references
References 154 publications
4
507
0
7
Order By: Relevance
“…Although the peak emission of donor–acceptor–donor (D‐A‐D) dyes and the tail emission of cyanine dyes can be both used for NIR‐II imaging, the benefit of NIR‐II imaging is better realized in the NIR‐IIb sub‐window (>1500 nm), where light can penetrate nearly all tissues . Imaging in the NIR‐IIb window can minimize photon scattering and simultaneously avoid high absorbance by water, affording high resolution of mouse vasculature at depths of several millimeter in the brain or other tissues .…”
mentioning
confidence: 99%
“…Although the peak emission of donor–acceptor–donor (D‐A‐D) dyes and the tail emission of cyanine dyes can be both used for NIR‐II imaging, the benefit of NIR‐II imaging is better realized in the NIR‐IIb sub‐window (>1500 nm), where light can penetrate nearly all tissues . Imaging in the NIR‐IIb window can minimize photon scattering and simultaneously avoid high absorbance by water, affording high resolution of mouse vasculature at depths of several millimeter in the brain or other tissues .…”
mentioning
confidence: 99%
“…F luorescence imaging in the second near-infrared region (NIR-II, 1000-1700 nm) enables direct visualization and real-time feedback of deep biological structures with a miraculous degree of clarity than NIR-I (800-900 nm) due to further suppressed photon scattering and minimized autofluorescence [1][2][3][4][5][6][7] . Simulation and experimental results have revealed that the imaging performance in term of spatial and temporal resolution and penetration depth could be further enhanced by the NIR-IIb (1500-1700 nm) fluorophores due to almost zero autofluorescence and much lower photo scattering [8][9][10] .…”
mentioning
confidence: 99%
“…Nevertheless, ICG has a low photostability and a low fluorescence quantum yield . Such has motivated the encapsulation of other heptamethine cyanines (e.g., IR780, IR808, IR825) that exhibit improved optical properties in nanostructures for cancer phototheragnostic …”
Section: Introductionmentioning
confidence: 99%